Identification of genetic elements required for Listeria monocytogenes growth under limited nutrient conditions and virulence by a screening of transposon insertion library - Narayanan, Lakshmi; Ozdemir, Ozan; Alugubelly, Navatha; Ramachandran, Reshma; Banes, Michelle; Lawrence, Mark; Abdelhamed, Hossam (Frontiers in Microbiology, 2022)
Listeria monocytogenes, the causative agent of listeriosis, displays a lifestyle ranging from saprophytes in the soil to pathogenic as a facultative intracellular parasite in host cells. In the current study, a random transposon (Tn) insertion library was constructed in L. monocytogenes strain F2365 and screened to identify genes and pathways affecting in vitro growth and fitness in minimal medium (MM) containing different single carbohydrate as the sole carbon source. About 2,000 Tn-mutants were screened for impaired growth in MM with one of the following carbon sources: glucose, fructose, mannose, mannitol, sucrose, glycerol, and glucose 6-phosphate (G6P). Impaired or abolished growth of L. monocytogenes was observed for twenty-one Tn-mutants with disruptions in genes encoding purine biosynthesis enzymes (purL, purC, purA, and purM), pyrimidine biosynthesis proteins (pyrE and pyrC), ATP synthase (atpI and atpD2), branched-chain fatty acids (BCFA) synthesis enzyme (bkdA1), a putative lipoprotein (LMOF2365_2387 described as LP2387), dUTPase family protein (dUTPase), and two hypothetical proteins. All Tn-mutants, except the atpD2 mutant, grew as efficiently as wild-type strain in a nutrient rich media. The virulence of twenty-one Tn-mutants was assessed in mice at 72 h following intravenous (IV) infection. The most attenuated mutants had Tn insertions in purA, hypothetical protein (LMOf2365_0064 described as HP64), bkdA1, dUTPase, LP2387, and atpD2, confirming the important role of these genes in pathogenesis. Six Tn-mutants were then tested for ability to replicate intracellularly in murine macrophage J774.1 cells. Significant intracellular growth defects were observed in two Tn-mutants with insertions in purA and HP64 genes, suggesting that an intact purine biosynthesis pathway is important for intracellular growth of L. monocytogens. These findings may not be fully generalized to all of L. monocytogenes strains due to their genetic diversity. In conclusion, Tn-mutagenesis identified that biosynthesis of purines, pyrimidines, ATP, and BCFA are important for L. monocytogens pathogenesis. Purine and pyrimidine auxotrophs play an important role in the pathogenicity in other bacterial pathogens, but our study also revealed new proteins essential for both growth in MM and L. monocytogenes strain F2365 virulence.